The Usefulness of the QR Code in Orthotic Applications after Orthopedic Surgery - Jaeho Cho (Healthcare, 2021)
The purpose of this study is to evaluate the utility of QR (quick response) codes in explaining the proper method for orthotic use after orthopedic surgery. A questionnaire survey was adopted to evaluate patient satisfaction with education and training in orthotic applications after orthopedic surgery. The study periods were 1 April to 30 April 2017, and 1 October to 31 October 2017. The oral training involving the conventional orthoses was conducted in April, and the videos with the orthosis on the QR code were captured in October. The QR code containing the data was distributed and the education was conducted. A total of 68 patients (QR-code group: 33) participated in the questionnaire survey. After the QR code application, the number of retraining cases increased from 62.9 to 93.9% (p-value < 0.01). The mean scores of the four items measuring the comprehension increased from 10.97 to 14.39. The satisfaction level rose from 7.14 to 9.30, and the performance increased from 7.14 to 9.52 (p-value < 0.01). The QR code is expected to be a valuable method for explaining the orthotic application after orthopedic surgery, and especially when repeated explanations are needed for elderly patients.